UPAYA PENINGKATAN PRODUKTIVITAS DAN PEMASARAN PRODUK FROZEN FOOD - Herlina, Herlina; Slamet, Puji; Ramadhan, Gilang; Maulana Ibrahim, Khusnul (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Sari Nikmat’s Frozen food UKM located in Malang, East Java faces problems in the process of refining refined sugar that is included in frozen donut packaging products. The process of refining refined sugar so far has been carried out manually by workers using plastic spoons and put into plastic clips. The process makes the dose is not precise and more varied. The next problem, the packaging owned by Sari Nikmat’s Frozen food UKM is the same size while there are many requests from customers to make large sized packaging. The Sari Nikmat’s Frozen food UKM have not yet thought about how to design large sized packaging. In terms of marketing, Sari Nikmat UKM has several distributors, the majority of which are in housing, the UKM wants to make a banner design as a promotional medium for the availability of Sari Nikmat frozen food products at the distributor’s location. As a proposal for the completion of this Community Partnership Program is the procurement of digital scales that can increase the productivity and precision of packaging refined sugar, making packaging designs for larger sizes, and making banner designs for information on product availability to be installed at several distributors.